Youth Participation in Agricultural Enterprises as Rural Job Creation Work and Its Determinants in Southern Ethiopia - Kassa Tarekegn; Kusse Kamaylo; Duge Galtsa; Endrias Oyka (Advances in Agriculture)
Even though agriculture has ample potential to absorb a large number of people, youths tend to stand away from the subsector. As a result, rural job creation works were started in southern Ethiopia by participating youth in different agricultural enterprises in the form of groups and cooperatives. However, as compared to sector potential, youths are not participating in agricultural job creation works in Ethiopia. Therefore, this study was intended to assess factors affecting youth participation in agricultural enterprises in selected districts of Southern Ethiopia. A multistage sampling procedure was followed to select 160 sample youths. The collected data from sampled youths were analyzed by both descriptive statistics and a probit econometric model. Among the agricultural enterprises, the majority of the youths (63.3%) preferred livestock enterprises indicating livestock sector job creation capacity in Ethiopia. The seasonal nature of agricultural income, fear of agricultural risk, and lack of initial capital were the top three factors hindering youth participation in the agricultural enterprise as rural job creation works. The probit model result shows that, among the hypothesized variables, education level, credit getting bureaucracy, lack of initial capital, fear of the group, risk and uncertainty, and lack of working place determine significantly youth participation in agriculture enterprises. Hence, respective bodies must group youths based on their preferred interest and evaluate their business plan critical before credit disbursement, while solving credit providing terms problems on the microfinance side and the introduction of agricultural insurance through these youth agricultural enterprises for agricultural risk fear needs stakeholders’ interventions. Overall, initial savings, interest rate, and payback period of credit need special policy adjustments to increase youth participation in an agricultural enterprise.